Pretreatment platelet count predicts survival outcome of patients with de novo non-M3 acute myeloid leukemia - Qianying Zhang (PeerJ, 2017)
Background Pretreatment platelet count has been reported as a potential tool to predict survival outcome in several solid tumors. However, the predictive value of pretreatment platelet count remains obscure in de novo acute myeloid leukemia (AML) excluding acute promyelocytic leukemia (M3). Methods We conducted a retrospective review of 209 patients with de novo non-M3 AML in our institute over a period of 8 years (2007–2015). Receiver operating characteristic (ROC) curve analysis was used to determine the optimal platelet (PLT) cutoff in patients. We analyzed the overall survival (OS) and disease free survival (DFS) using the log-rank test and Cox regression analysis. Results By defining the platelet count 50 × 109/L and 120 × 109/L as two cut-off points, we categorized the patients into three groups: low (<50 × 109/L), medium (50–120 × 109/L) and high (>120 × 109/L). On univariate analysis, patients with medium platelet count had longer OS and DFS than those with low or high platelet count. However, the multivariate analysis showed that only longer DFS was observed in patients with medium platelet count than those with low or high platelet count. Conclusion Our findings indicate that pretreatment platelet count has a predictive value for the prognosis of patients with non-M3 AML.